Variability of spring ecosystem water use efficiency in Northeast Asia and its linkage to the Polar-Eurasia pattern - Ning Xin; Botao Zhou; Haishan Chen; Shanlei Sun (Environmental Research Letters, 2023)
Given that water use efficiency (WUE) is an important indicator to measure the trade-off between carbon uptake and water consumption within the ecosystem, better understanding the variation of ecosystem WUE and related driving factors is of great interest. In this study, the variability of spring ecosystem WUE in Northeast Asia (NEA) was investigated. The results show that its primary mode exhibits a monosign variation. This mode is directly controlled by the variability of gross primary productivity. The climate conditions also play remarkable roles, featuring that warm surface air temperature (high soil moisture) favors enhanced ecosystem WUE in northern (southern) NEA. Further analysis reveals that the Polar-Eurasia (POL) pattern can significantly impact the variability of spring ecosystem WUE in NEA through changing surface air temperature and soil moisture. When the POL pattern lies in the positive phase during spring, anticyclonic circulation anomalies with an equivalent barotropic structure prevail over northern NEA, concurrent with anomalous easterlies over southern NEA and a weakening of the East Asian jet (EAJ). Accordingly, anomalous downward motion is introduced over northern NEA, resulting in higher surface air temperature which is beneficial for the increase of local ecosystem WUE. Meanwhile, the easterly anomalies help to increase water vapor transport into southern NEA and the weakened EAJ can induce anomalous ascending over southern NEA, favoring the increase of precipitation and hence soil moisture, which consequently enhances the ecosystem WUE in southern NEA.